Adaptive strategies of Egyptian crowfoot grass (Dactyloctenium aegyptium (L.) Willd): Germination responses to environmental factors - Ahmad Zare; Elham Elahifard; Zahra Asadinejad (PLoS ONE, 2026)
Egyptian crowfoot grass (Dactyloctenium aegyptium (L.) Willd.) is a troublesome C 4 grass weed that competes with crops such as rice (Direct Seeded Rice), sugarcane and urban green space. The effects of constant and alternating temperatures, storage times, light, salinity, and water stress on germination of Egyptian crowfoot grass studied under laboratory conditions. Germination was stimulated by light, and seed germination percentage was higher under alternative temperatures compared to constant temperatures. Results also showed that germination percentage increased as the storage period lengthened. The highest germination percentage (97.33%) was observed under 30/20°C alternating temperature with light in seeds stored for 12 months. The time required to reach maximum germination was shorter under both constant and alternating temperatures for seeds stored for 12 months compared to those stored for 5 months and 2 months, respectively. Osmotic stress had moderate negative effects on germination, with 45% of the Egyptian crowfoot grass seeds able to germinate at −0.6 MPa,. Complete germination inhibition was observed at an osmotic potential of −1 MPa. The osmotic potential required for 50% inhibition of maximum germination was 0.49 MPa. Also results of salinity indicated that 23% of seeds germinated at sodium chloride (NaCl) concentration of 200 mM. A 50% reduction in germination of Egyptian crowfoot grass was caused 162 mM. To reduce the soil seed bank of this photoblastic weed, we recommend implementing deep tillage, applying straw mulch, and utilizing the false and stale seedbed techniques.